2012
DOI: 10.1097/igc.0b013e3182571479
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy as Part of Primary Cytoreductive Surgery for Advanced Ovarian Cancer: A Retrospective Cohort Study

Abstract: Splenectomy at the time of primary cytoreductive surgery for advanced ovarian cancer may contribute to achieve complete cytoreduction with low perioperative complication rate. This procedure seems to be an acceptable and rational intervention to increase the survival rates of those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…Searching the literature database (PubMed, Embase, Medscape) using the criteria of recurrence, solitary, splenic, ovarian cancer and tubal cancer and the references of retrieved articles, we found 35 cases of splenectomy for recurrent TOC (table 1) [5,6,8,26,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. Splenectomy was mainly part of secondary cytoreductive surgery and only in one case of tertiary cytoreduction [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Searching the literature database (PubMed, Embase, Medscape) using the criteria of recurrence, solitary, splenic, ovarian cancer and tubal cancer and the references of retrieved articles, we found 35 cases of splenectomy for recurrent TOC (table 1) [5,6,8,26,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. Splenectomy was mainly part of secondary cytoreductive surgery and only in one case of tertiary cytoreduction [43].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [28,29,30] compared perioperative details and follow-up data between patients who underwent splenectomy and those who did not in the setting of primary cytoreductive surgery for advanced ETOC. No significant differences were observed between groups, leading to the conclusion that this procedure seems to be an acceptable and rational intervention to increase the chances of optimal cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoreduction may include a variety of surgical procedures such as bowel resection, especially rectosigmoid (which is necessary in approximately 30–50% of cases of advanced ovarian cancer), diaphragm stripping, peritoneal resection, splenectomy, partial hepatic or pancreatic resection, cholecystectomy, hysterectomy, and salpingo-oophorectomy [ 4 , 12 – 13 , 16 – 18 ].…”
Section: Primary Cytoreductionmentioning
confidence: 99%
“…[12] Splenectomy, for instance, has been evaluated as a safe practice at the time of primary cytoreductive surgery for ovarian cancer, offering better cytoreduction, with low perioperative complication rate. [13] Colon resection, most often rectosigmoidectomy followed by a primary anastomosis, has been found to have a positive impact on survival, [14] improving disease free and overall survival, [15] with an acceptable postoperative quality of life and without a delay on adjuvant systemic chemotherapy. [16] The significance of optimal cytoreduction can be demonstrated also on a microscopic level, since it has been found that intraperitoneal chemotherapy agents under hyperthermic conditions can penetrate tissue to a depth of only 2 to 3 milimeters, [17] therefore HIPEC administration can only be efficient given that meticulous resection has been performed, leaving residual tumor of less than 1 mm -2 mm in thickness.…”
Section: The Role Of Cytoreductive Surgerymentioning
confidence: 99%